Sistema de gerenciamento de resíduos sólidos : resíduo legal - Santos, Carlos Alexandre Silva Alves dos (2022)
This work presents the Solid Waste Management System – Legal Waste project, whose objective is to develop a management and control system for the collection, transport and disposal of solid waste for solid waste managers and for large waste generators such as agribusiness companies in the state of Mato Grosso. As this system is part of a solution to the problems found in companies linked to the agricultural and livestock sector in the state, coming to meet Agriculture 4.0. The system consists of a WEB platform, with mobile interaction and database application for the presentation and extraction of systematized information and reports, being an innovative solution, applied to various segments of the state's economic matrix, such as agribusiness, environment / bioeconomy, transport and logistics. Using the Design Science Research guidelines, it was possible to validate the stages of development of the work, from the identification of the problem to the description of the proposed technological solution. The technological innovation of the solution is described as a management control system for solid waste collection, with systematized data and information on field collections available on a WEB platform, with the application of big data and the internet of things. Having the ability to extract dynamic reports from the system by period, location, client, according to the credentials, access levels and needs of users, as the management system monitors the collection and disposal of solid waste, with point control to the point, giving the process greater transparency and interaction between those involved. With the development of the work, it was possible to develop the software itself in its MVP version, register with the INPI, prepare scientific articles during the research and the conclusive technical report with the description of the activities.